The exploitation of women’s body in the practice of Warung Kopi Pangku - Ferry Wahyu Arladin (Faculty of Social and Political Science, Universitas Airlangga, 2019)
This study focuses on examining the exploitation of women’s bodies in the social practice of warung kopi pangku in Jombang. A woman’s body considered to be an object used to attract consumers, as evidenced by their appearance as a sexy maid, whether through the minimalist clothing worn or excessive preening. Warung kopi pangku also provides sensuality through the body of waitresses. Their activities include not only just making orders but also accompanying the consumers who are enjoying their coffee. The waitresses’ body becomes a power regulation target, namely when they targeted for arrest during raids. Warung kopi pangku currently exists. Many visitors come to the shops and the women employed have not reduced in number. This study attempts to describe the forms of human exploitation that occur concerning the waitresses in the specific situation of warung kopi pangku. This study used a qualitative research method with a critical paradigm. Collecting the data was done through in-depth interviews to 14 informants consisting of waitresses, consumers and the owner of warung kopi pangku. To dismantle the problems, we used the theoretical perspective of Michel Foucault on the power of the body. The results of the study showed that the bodily exploitation of waitresses could occur in various situations. The appearance of the waitresses is the most visible aspect that involves exploitation. It was proven through the beautiful body image of waitresses being used to provoking consumer sexual desire. Bodily exploitation was also done through the control of the work activity of the waitresses. They have to provide an entertaining atmosphere while accompanying the consumers. The exploitation also occurred in the covert prostitution practice. There were sexual transactions conducted in warung kopi pangku, so the waitresses’ bodies were reduced to a satisfaction tool for sexual needs. The bodily exploitation of the waitresses was a powerful strategy to condition the body as an effort to support the existence of warung kopi pangku. The waitresses’ bodies were controlled through discursive practices; therefore, the exploitation was not considered to be a problem.